PENERAPAN PENDEKATAN DISCOVERY LEARNING UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK ASPEK PENGETAHUAN - Jeno, Maria D I; H.B. Hayon, Vinsensia; Tukan, Maria Benedikta (Jurnal Suluh Pendidikan, 2025)
The purpose of this study was to determine the ability of teachers in managing learning that applies the discovery learning approach, the completeness of student learning outcomes, the completeness of indicators, and the improvement of student learning outcomes in terms of applying the discovery learning approach. The results of the study showed that the ability of teachers in managing learning that applies the discovery learning approach on colloid material for class XI IPA SMAN 2 Kota Komba is classified as good with an average score obtained of 3.97; The overall learning outcomes of students on colloid material in learning that applies the discovery learning approach SMAN 2 Kota Komba are complete with an average final score obtained of 86; The learning outcome indicators of students in learning that applies the discovery learning approach for class XI IPA SMAN 2 Kota Komba are complete with an average score of 0.96; there is an increase in student learning outcomes in applying the discovery learning approach for class XI IPA SMAN 2 Kota Komba which is high with an average score of 0.73.